2020
DOI: 10.1186/s12889-020-8225-8
|View full text |Cite
|
Sign up to set email alerts
|

More Guidelines than states: variations in U.S. lead screening and management guidance and impacts on shareable CDS development

Abstract: Background: Pediatric lead exposure in the United States (U.S.) remains a preventable public health crisis. Shareable electronic clinical decision support (CDS) could improve lead screening and management. However, discrepancies between federal, state and local recommendations could present significant challenges for implementation. Methods: We identified publically available guidance on lead screening and management. We extracted definitions for elevated lead and recommendations for screening, follow-up, repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…This finding may have clinical implications, as this study as well as a recent national study has demonstrated increased risk of detectable and elevated blood lead levels after 24 months of age. 35 There is currently great variability between individual states and CDC guidance on the frequency and at what ages to conduct universal or targeted blood lead testing. 6,35 Lastly, we were not able to identify an etiology for the increase in the proportion of BLL ≥ 5 µg/dL (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding may have clinical implications, as this study as well as a recent national study has demonstrated increased risk of detectable and elevated blood lead levels after 24 months of age. 35 There is currently great variability between individual states and CDC guidance on the frequency and at what ages to conduct universal or targeted blood lead testing. 6,35 Lastly, we were not able to identify an etiology for the increase in the proportion of BLL ≥ 5 µg/dL (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…35 There is currently great variability between individual states and CDC guidance on the frequency and at what ages to conduct universal or targeted blood lead testing. 6,35 Lastly, we were not able to identify an etiology for the increase in the proportion of BLL ≥ 5 µg/dL (Fig. 5) in 2009.…”
Section: Discussionmentioning
confidence: 99%
“…Early identification of children with lead exposure can help identify and eliminate lead sources (and future exposures for other children); reduce their BLL over time; and link children with high BLLs to medical, nutritional, and educational services. Medicaid-enrolled children are required to be screened at ages 12 and 24 months; many states have additional screening requirements (4).…”
mentioning
confidence: 99%
“…As of 2020, in 43 states, 52 medical health care workers and medical facilities are required to report all child BLL results to state agencies for surveillance purposes. In the remaining states, reporting is based on a state‐defined benchmark.…”
Section: Summary Of Current Child Bll Testing Practicesmentioning
confidence: 99%